2021
DOI: 10.1007/s00284-021-02668-6
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Growth Dependent Succession of Culturable Endophytic Bacteria and Their Plant Growth Promoting Traits

Abstract: Endophytic bacteria present ubiquitously in all plant parts. Their community structure may vary depending on plant tissue and growth condition. This work mainly focused on exploring the diversity of culturable nitrogen-fixing endophytic bacteria in above-ground plant parts of wheat by harvesting it during various growth points (Seed stage, 1st, 2nd, and 3rd month old plants, respectively). Distinct endophytic bacterial colonies were selected on Jensen's agar plate. Based on the 16S rRNA sequencing, 43 putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(69 reference statements)
0
4
0
1
Order By: Relevance
“…Based on literature review, enriched ASVs in different groups were categorized as PGPR at the genus level [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ,…”
Section: Resultsmentioning
confidence: 99%
“…Based on literature review, enriched ASVs in different groups were categorized as PGPR at the genus level [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ,…”
Section: Resultsmentioning
confidence: 99%
“…The results were compared with those of grains sterilized with 4.5% NaOCl:water (1:1) for 20 min, which is known not to inhibit endophytic microorganisms ( Figure 4 ) ( Sahu et al., 2022 ). MALDI-TOF analysis of the microbial species revealed that neither treatment inhibited the growth of well-known endophytes, such as Aspergillus spp., Penicillium spp., and Staphylococcus spp Toghueo and Boyom, 2020 ; Patel at al., 2021 ; Pang at al., 2022 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of its bacterial strains (Exiguobacterium sp. WS1-12) were also noted to have a positive effect on root hair formation thus a positive effect on plant growth including grain (wheat) [82].…”
Section: Discussionmentioning
confidence: 98%
“…are aerobic, gram-stain-positive, non-spore-forming bacteria that is soil borne. Bacteria strains within this genome aid plant growth by assisting in phosphate solubilization [82]. They only grow within a pH range of 5 to 11 and a temperature of 10 °C to 37 °C , however growth optimums for temperature and pH are 25 °C and 7 respectively.…”
Section: Discussionmentioning
confidence: 99%